Managerial Role of Principals in Islamic Boarding School Quality: Peran Manajerial Kepala Sekolah dalam Kualitas Sekolah Asrama Islam - Bilal, Farid; Anita Puji Astutik (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The quality of Islamic educational institutions is strongly determined by the managerial capacity of principals as key leaders. Specific background: In boarding school settings, principals are not only responsible for administrative duties but also for ensuring holistic educational quality. Knowledge gap: Previous studies have often emphasized instructional leadership, yet limited research explores the comprehensive managerial functions of principals in Islamic boarding schools. Aim: This study aims to describe and analyze the managerial role of the principal in improving the quality of Islamic education institutions. Results: Using a qualitative approach with observation, interviews, and documentation at SMP Boarding School 09 Tanggulangin Sidoarjo, the findings reveal six core areas of principal’s managerial efforts: curriculum and learning management, human resource management, student management, facilities and infrastructure, financial management, and public relations. Novelty: This research highlights an integrated managerial framework that systematically strengthens institutional performance across multiple domains. Implications: The study underscores the strategic role of principals in sustaining quality improvement, offering insights for policymakers, school leaders, and stakeholders in Islamic education. Highlights: Principal’s managerial role is central to institutional quality. Six managerial domains strengthen Islamic boarding school development. Provides strategic insights for leadership in Islamic education. Keywords: Islamic Boarding School; Principal; Managerial Role; Quality Management; Education Policy